(untitled) (Physical Education, Health and Social Sciences, 2025)
Ginseng, a widely utilized medicinal herb in traditional Eastern medicine, is renowned for its diverse pharmacological properties. The primary phytoconstituents responsible for its therapeutic effects are ginsenosides, a class of triterpenoid saponins, along with polysaccharides, flavonoids, peptides, and polyacetylenes. These bioactive compounds contribute to ginseng’s adaptogenic, antioxidant, anti-inflammatory, immunomodulatory, neuroprotective, and anticancer activities. Ginsenosides, particularly Rb1, Rg1, Rg3, and Rh1, interact with multiple cellular signaling pathways such as MAPK, PI3K/Akt, and NF-κB, influencing processes like apoptosis, cell proliferation, and cytokine production. Ginseng polysaccharides enhance immune function by stimulating macrophage activity and increasing the secretion of interleukins and interferons. Moreover, ginseng improves cognitive function, regulates blood glucose levels, supports cardiovascular health, and exhibits protective effects against neurodegenerative diseases. Its pharmacodynamics involve modulation of neurotransmitter release, receptor sensitivity, ion channel activity, and enzyme inhibition. The herb’s multifaceted mechanisms of action reflect its potential as a complementary therapeutic agent in modern medicine. Current research supports its efficacy in managing conditions such as diabetes, cancer, cardiovascular disorders, and neurological dysfunctions. However, variations in ginseng species, extraction methods, and dosage necessitate further standardized studies to ensure its clinical safety and efficacy. Ginseng continues to be a focal point of phytopharmacological research with expanding global relevance.